A Novel Class of Hsp90 C‐Terminal Modulators Have Pre‐Clinical Efficacy in Prostate Tumor Cells Without Induction of a Heat Shock Response. Issue 16 (16th August 2016) - Armstrong, Heather K.; Koay, Yen Chin; Irani, Swati; Das, Rajdeep; Nassar, Zeyad D.; ,; Selth, Luke A.; Centenera, Margaret M.; McAlpine, Shelli R.; Butler, Lisa M.
Abstract : BACKGROUND: While there is compelling rationale to use heat shock protein 90 (Hsp90) inhibitors for treatment of advanced prostate cancer, agents that target the N‐terminal ATP‐binding site of Hsp90 have shown little clinical benefit. These N‐terminal binding agents induce a heat shock response that activates compensatory heat shock proteins, which is believed to contribute in part to the agents' lack of efficacy. Here, we describe the functional characterization of two novel agents, SM253 and SM258, that bind the N‐middle linker region of Hsp90, resulting in reduced client protein activation and preventing C‐terminal co‐chaperones and client proteins from binding to Hsp90. METHODS: Inhibition of Hsp90 activity in prostate cancer cells by SM253 and SM 258 was assessed by pull‐down assays. Cell viability, proliferation and apoptosis were assayed in prostate cancer cell lines (LNCaP, 22Rv1, PC‐3) cultured with N‐terminal Hsp90 inhibitors (AUY922, 17‐AAG), SM253 or SM258. Expression of HSR heat shock proteins, Hsp90 client proteins and co‐chaperones was assessed by immunoblotting. Efficacy of the SM compounds was evaluated in human primary prostate tumors cultured ex vivo by immunohistochemical detection of Hsp70 and Ki67. RESULTS: SM253 and SM258 exhibit antiproliferative and pro‐apoptotic activity in multiple prostate cancer cell lines (LNCaP, 22Rv1, and PC‐3) at low micromolar concentrations. Unlike the N‐terminal inhibitors AUY922 and 17‐AAG, these SM agents do not induce expression of Hsp27, Hsp40, or Hsp70, proteins that are characteristic of the heat shock response, in any of the prostate cell lines analyzed. Notably, SM258 significantly reduced proliferation within 2 days in human primary prostate tumors cultured ex vivo, without the significant induction of Hsp70 that was caused by AUY922 in the tissues. CONCLUSIONS: Our findings provide the first evidence of efficacy of this class of C‐terminal modulators of Hsp90 in human prostate tumors, and indicate that further evaluation of these promising new agents is warranted. Prostate 76:1546–1559, 2016 . © 2016 Wiley Periodicals, Inc.